The role of SLC2A1 mutations in myoclonic astatic epilepsy and absence epilepsy, and the estimated frequency of GLUT1 deficiency syndrome. (5th November 2015) - Larsen, Jan; Johannesen, Katrine Marie; Ek, Jakob; Tang, Shan; Marini, Carla; Blichfeldt, Susanne; Kibæk, Maria; von Spiczak, Sarah; Weckhuysen, Sarah; Frangu, Mimoza; Neubauer, Bernd Axel; Uldall, Peter; et al.
Summary: The first mutations identified in SLC2A1, encoding the glucose transporter type 1 (GLUT1) protein of the blood–brain barrier, were associated with severe epileptic encephalopathy. Recently, dominant SLC2A1 mutations were found in rare autosomal dominant families with various forms of epilepsy including early onset absence epilepsy (EOAE), myoclonic astatic epilepsy (MAE), and genetic generalized epilepsy (GGE). Our study aimed to investigate the possible role of SLC2A1 in various forms of epilepsy including MAE and absence epilepsy with early onset. We also aimed to estimate the frequency of GLUT1 deficiency syndrome in the Danish population. One hundred twenty patients with MAE, 50 patients with absence epilepsy, and 37 patients with unselected epilepsies, intellectual disability (ID), and/or various movement disorders were screened for mutations in SLC2A1 . Mutations in SLC2A1 were detected in 5 (10%) of 50 patients with absence epilepsy, and in one (2.7%) of 37 patient with unselected epilepsies, ID, and/or various movement disorders. None of the 120 MAE patients harbored SLC2A1 mutations. We estimated the frequency of SLC2A1 mutations in the Danish population to be approximately 1:83, 000. Our study confirmed the role of SLC2A1 mutations in absence epilepsy with early onset. However, our study failed to support the notion that SLC2A1 aberrations are a cause of MAE without associated features such as movement disorders.